Most human proteins made in both nucleus and cytoplasm turn over within minutes - Baboo, S; Bhushan, B; Jiang, H; Grovenor, C; Pierre, P; Davis, B; Cook, P (Public Library of Science, 2014)
In bacteria, protein synthesis can be coupled to transcription, but in eukaryotes it is believed to occur solely in the cytoplasm. Using pulses as short as 5 s, we find that three analogues--L-azidohomoalanine, puromycin (detected after attaching fluors using 'click' chemistry or immuno-labeling), and amino acids tagged with 'heavy' 15N and 13C (detected using secondary ion mass spectrometry)--are incorporated into the nucleus and cytoplasm in a process sensitive to translational inhibitors. The nuclear incorporation represents a significant fraction of the total, and labels in both compartments have half-lives of less than a minute; results are consistent with most newly-made peptides being destroyed soon after they are made. As nascent RNA bearing a premature termination codon (detected by fluorescence in situ hybridization) is also eliminated by a mechanism sensitive to a translational inhibitor, the nuclear turnover of peptides is probably a by-product of proof-reading the RNA for stop codons (a process known as nonsense-mediated decay). We speculate that the apparently-wasteful turnover of this previously-hidden ('dark-matter') world of peptide is involved in regulating protein production.